Peran Strategi Pembelajaran Diferensiasi dalam Meningkatkan Kualitas Pendidikan Islam - Khalib Gadafi; Andika Saputra; Gusmaneli Gusmaneli (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to examine the role of differentiated instruction strategies in improving the quality of Islamic education. Using a qualitative descriptive approach through literature review, this research analyzes the concept, implementation, and impact of differentiation strategies on the effectiveness of learning in Islamic education. Differentiated instruction allows for the adaptation of teaching methods based on students' needs, learning styles, and individual potential, creating a more inclusive and adaptive learning environment. The findings indicate that implementing differentiation strategies whether in content, process, or product significantly enhances students' understanding of Islamic teachings. Additionally, these strategies increase students' learning motivation, active engagement, and help them develop character aligned with Islamic values. Teachers who apply differentiation strategies can be more flexible in delivering material and more responsive to individual student differences, making the learning process more effective and meaningful. The implications of this research emphasize that differentiation strategies play a crucial role in creating a higher-quality Islamic education system that remains relevant in an evolving era. Therefore, continuous efforts from educators and educational institutions are needed to adopt these strategies in order to produce a generation of Muslims who not only have a strong understanding of Islamic teachings but also possess the adaptability and moral character to face modern life challenges.